2008
DOI: 10.1038/onc.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of methionine aminopeptidase-2 causes cell transformation and stimulates proliferation

Abstract: Methionine aminopeptidase-2 (MetAP2) processes N-terminal methionine from nascent cellular proteins. Inhibition of MetAP2 has been shown to block angiogenesis and suppress tumor growth in preclinical tumor models. However, the biological role of MetAP2 in cancer is not well understood. We examined the effect of three distinct chemical classes of MetAP2 inhibitors on the growth of a panel of human cancer cells in vitro. All MetAP2 inhibitors caused inhibition of tumor cell growth in both anchorage-dependent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…The antiproliferative activity of A-800141 was not limited to endothelial cells, as originally proposed for fumagillin and TNP-470 (16), but extended to many tumor cell lines as well, which is described in detail elsewhere (25). The antiproliferative activity of the sulfonamide series of inhibitors has been shown to correlate tightly with their cellular activity inhibiting MetAP2 enzyme function (21).…”
Section: Resultsmentioning
confidence: 76%
“…The antiproliferative activity of A-800141 was not limited to endothelial cells, as originally proposed for fumagillin and TNP-470 (16), but extended to many tumor cell lines as well, which is described in detail elsewhere (25). The antiproliferative activity of the sulfonamide series of inhibitors has been shown to correlate tightly with their cellular activity inhibiting MetAP2 enzyme function (21).…”
Section: Resultsmentioning
confidence: 76%
“…The normalized CI is an arbitrary unit derived from electrical impedance measurement (19)(20)(21)(22). The correlation between CI and cell viability is well documented in the literature (23)(24)(25)(26). Furthermore, we also tested cell death and apoptosis in three selected tumor lines, A549, HT29, and SH-SY5Y, treated with 1 μmol/L BFBTS, the concentration approximating the IC 50 value for cell proliferation and cytotoxicity (Table 1).…”
Section: Inhibition Of Cancer Cell Proliferation and Induction Of Apomentioning
confidence: 95%
“…Furthermore, various Src family tyrosine kinases, ADP ribosylation factors and eukaryotic transcription elongation factor-2 were substrates of MetAP2 which plays a significant role in the progression of metastasis (Tucker et al, 2008). A derivative of the natural product fumagillin, TNP470 has been shown to be safe and effective in the treatment of solid tumors in several animal studies and preclinical trials.…”
Section: Metap2 Inhibitorsmentioning
confidence: 99%
“…It has been reported that MetAP2 could function as an oncogene (Tucker et al, 2008). Furthermore, various Src family tyrosine kinases, ADP ribosylation factors and eukaryotic transcription elongation factor-2 were substrates of MetAP2 which plays a significant role in the progression of metastasis (Tucker et al, 2008).…”
Section: Metap2 Inhibitorsmentioning
confidence: 99%